TELAAH TEOLOGI PENTAKOSTA MEMAKNAI PEMELIHARAAN ALLAH BAGI ORANG PERCAYA DI MASA NEW NORMAL - Kosma Manurung (Sekolah Tinggi Teologi Imauel Pacet, 2021)
The God of the Bible is very different from God as understood by the deism where God does not care about the existence of human creation, the God of the Bible is a God who loves and cares about human existence. The Biblical description of God that Pentecostals also believe is a God who loves, cares for, and is fully responsible for His chosen people. The purpose of this research is to explain the meaning of Pentecostal theology towards God's providence. Researchers used descriptive analysis methods and literature review. This article contains biblical narratives in both the Old and New Testaments about God's providence and the meaning of God's providence. Based on the results of this study, it can be concluded that God's provision is God's responsibility towards His chosen people, and in God's care there is His presence. God's provision also talks about God's provision, how God provides for the needs of His people, which is also a manifestation of His love.Allah di Alkitab sangat berbeda dengan Allah seperti yang difahami kaum deisme dimana Allah tidak perduli dengan keberadaan manusia ciptaannya, Allah di Alkitab adalah Allah yang mengasihi dan peduli terhadap keberadaan manusia. Gambaran Alkitab tentang Allah yang juga diyakini kaum Pentakosta adalah Allah yang mengasihi, peduli, dan bertanggung jawab penuh terhadap umat pilihan-Nya. Maksud dari penelitian ini ingin menjelaskan pemaknaan teologi Pentakosta terhadap pemeliharaan Allah. Peneliti menggunakan metode deskriptif analisis dan kajian literatur. Artikel ini berisikan narasi Alkitab baik di Perjanjian Lama maupun di Perjanjian Baru tentang pemeliharaan Allah dan juga pemaknaan pemeliharaan Allah. Berdasarkan hasil penelitian ini didapat kesimpulan bahwa pemeliharaan Allah merupakan tanggung jawab Allah terhadap umat pilihan-Nya, dan dalam pemeliharaan Allah ada penyertaan-Nya. Pemeliharaan Allah juga berbicara tentang penyediaan Allah bagaimana Allah menyediakan kebutuhan umat-Nya yang juga merupakan wujud nyata dari kasih-Nya.